Effectiveness of Avocado Seed Extract (Persea Americana Mill) in Maintaining Fibroblast Cell Viability of Avulsed Teeth in Male Wistar Rats - Dila Rohmaniar; dzanuar rahmawan; basma rosandi prakosa (LP2M IIK (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan) Bhakti Wiy, 2023)
Background: Avulsion is a complex trauma characterized by the loss of a tooth from its socket. An avulsion condition requires immediate replantation to return the tooth to its socket. The success of this action is influenced by the viability of the fibroblast cells. One of the measures to maintain viability is to store avulsed teeth in storage media. Avocado seed (Persea Americana Mill) is a plant that is easily available and contains flavonoids and saponins which have anti-inflammatory, antioxidant and antibacterial activities. Avocado seed extract is known to play a role in wound healing by increasing the number of fibroblast cells. Objective: to determine the effectiveness of avocado seed extract (Persea Americana Mill) in maintaining the viability of avulsed tooth fibroblast cells in male Wistar rats. Methods: The sample used was 24 Wistar rat teeth extracted and divided into 2 groups, 1 control group and 1 treatment group, where each group was divided into 2 subgroups based on soaking time, namely 30 and 60 minutes. Furthermore, fibroblast cells in the periodontal ligament are trypsinated and then counted with a hemocytometer on a light microscope. The data were then tested using SPSS 24 software. Results: There was a significant difference in the amount of fibroblast cell viability in immersion using avocado seed extract and HBSS. Conclusion: Soaking using HBSS for 30 minutes produced the best fibroblast cell viability.